Avaliação de estratégias para a redução do consumo de água de abastecimento como meio de diminuição da pressão sobre os recursos hídricos - Erick Brizon D'angelo Chaib (2016)
In a scenario of relative water scarcity, it is advisable to implement public policies aimed at maintaining adequate potable water supply. Since residential water use represents a significant portion of the total volume of drinking water consumed in urban areas, thus adoptions of measures to reduce household water consumption are important. In this context, the present research focuses the evaluation of some technological saving devices (such as rainwater harvesting, use of economical hydraulic equipments and individual metering of water consumption in multifamily buildings) that may provide reduction of potable water consumption within the household in the territorial scale of large urban areas. Therefore, existing single-family dwellings and multifamily buildings in the city was organized based on the distributions of their characteristics such as roof areas, construction standards and heights. The city of Belo Horizonte city, Minas Gerais state´s capital, was used as a case study. The variability of existing dwellings and buildings were reduced by the correlations with residential standard-designs (5 single-family and 10 multifamily buildings), standardizing their constructive characteristics. After, based on the standard-designs, hydraulic and financial simulations to evaluate the performance of the water saving devices (in the case of rainwater harvesting systems were done through simulation using a 25-year daily rainfall time series) were done. The results were extrapolated to municipal level, considering the hypothesis of widespread use in the city, indicated the potential of potable water saving in relation to the annual household consumption of potable water in the order of 19.5% for rainwater harvesting, 24,7% for water saving devices and 15.7% for individualized water metering systems in buildings. For rainwater harvesting systems, financial results, from the perspective of a private investor, results indicated infeasibility for low constructive standard dwellings and buildings, while for normal and high standard, it has shown the systems feasibility, although with high payback periods. As for the other equipment, due to the fact that they have lower implementation, operation and maintenance costs, financial results showed shorter payback periods when compared to rainwater harvesting systems. These results suggest that the dissemination of these systems may require the proposal of conception and evaluation concerning the regulatory and funding models, and other economic tools as well to promote them for large-scale use, to reduce the pressure on water resources.